Analysis of risk factors for gestational hypertension and preeclampsia: Literature review - Hayati, Thursina Vera; M. Zulkarnain, M. Zulkarnain; Flora, Rostika; Fajar, Nur Alam; Rahmiwati, Anita; Ocktariyana, Ocktariyana; Ariana, Rika (Institute of Computer Science (IOCS), 2024)
Based on Disability Adjusted Life Years (DALYs), there are four main disease burdens, namely ischemic heart disease, cerebrovascular disease (including stroke and hypertension), diabetes and tuberculosis infectious disease. Gestational hypertension is very closely related to CVD (cardiovascular disease) with the potential for preeclampsia to have an impact on premature birth or small babies for the gestational age, stillbirths, low birth weight babies, etc. The research objective was to analyze the risk factors for gestational hypertension and preeclampsia. Methods: This study is a literature review based on the PRISMA guidelines. using electronic databases namely Google scholar, Sciencedirect and Pubmed with a period from 2017 to 2022 with the keywords